Globalization and wage inequality - National Bureau of Economic Research, Cambridge; Helpman, Elhanan (Cambridge, MA, 2016)
"Globalization has been blamed for rising inequality in rich and poor countries. Yet the views of many protagonists in this debate are not based on evidence. To help form an evidence-based opinion, I review in this paper the theoretical and empirical literature on the relationship between globalization and wage inequality. While the initial analysis that started in the early 1990s focused on a particular mechanism that links trade to wages, subsequent studies have considered several other channels, and the quantitative assessment of the size of these influences has been carried out in multiple studies. Building on this research, I conclude that trade played an appreciable role in increasing wage inequality, but that its cumulative effect has been modest, and that globalization does not explain the preponderance of the rise in wage inequality within countries."